HADIS TEMATIK ANTROPOMORFISME - Uqbatul Khoir Rambe (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
The word "anthropomorphism" is derived from English "anthropomorphism" which comes from the Greek "anthropos" (human) and "morphe" (form). In Islamic teachings, anthropomorphism is identified with "tasybîh" or "tajassum" . T ashbîh means to resemble something with something else. In theological terms, tasybîh means the likeness of God with humans in the form and attributes of Him. Whereas tajassum means the depiction of the body of God as found in humans. That doctrinal anthropomorphism is a necessity and is evident both in the hadith and the Koran. The amount even so much, can reach hundreds. From the hadith of the Messenger of Allah it was found that the holy riots were claimed by Bukhori and Muslim. When viewed from Mukhorrij it is strongly believed that the hadith is very true, and there is no reason to reject it. While at the level of thought, both in sarah and in the opinions of scholars, theologians and Sufis found their thoughts varied.Each argues that supports their thinking. Nothing can take precedence over the others, because all interpretations are intended to establish the right acceptance of Allah SWT. Wallohu a bus showab